Framing the President: the Dominant Ideology – Comprehensive Repertoire of News Frames // Enquadrando o Presidente: a ideologia dominante – repertório compreensivo dos quadros midiáticos - Schiff, Frederick (Contemporanea, 2011)
The theory of a dominant ideology underlying the news remains unacceptable for the commercial press and undermines its legitimacy. For social constructionists, no description or categorization is neutral. If all reporting has a point of view and the news inherently evaluates and frames events, the heuristic task is to demonstrate the existence of a single inventory of repeatedly used and shared “stock phrases” that consistently interpret “objective” events. Our case study examines coverage of U.S. President Bill Clinton in his first two years. Despite the wide number of events occurring and the large number of articles reviewed (N=513), the Clinton presidency was consistently portrayed using a finite and relatively small number of frames. We provide preliminary evidence of an industry-wide inventory of frames used by news workers over time and in a range of newsroom settings.